Interactions between deep formation fluid and gas hydrate dynamics inferred from pore fluid geochemistry at active pockmarks of the Vestnesa Ridge, west Svalbard margin - Hong, W.-L.; Pape, T.; Schmidt, C.; Yao, H.; Wallmann, K.; Plaza-Faverola, A.; Rae, J.W.B.; Lepland, A.; Bünz, S.; Bohrmann, G. (Marine and Petroleum Geology, 2021)
Cruise MSM57-1/-2 was funded by the German Research Foundation ( DFG ), the Research Center/Excellence Cluster “The Ocean in the Earth System” at MARUM–Center for Marine and Environmental Sciences, University of Bremen and funds from CAGE. This work is partly supported by the Research Council of Norway (RCN) through Petromaks2-NORCRUST (project number 255150 ) and the Centre of Excellence funding scheme for CAGE (project number 223259 ). APF’s contribution was part of the SEAMSTRESS project supported by starting grants from the Tromsø Research Foundation and the Research Council of Norway (grant nr. 2878659 ). Seafloor seepage sites along the Vestnesa Ridge off west-Svalbard have been, for decades, a natural laboratory for the studies of fluid flow and gas hydrate dynamics along passive continental margins. The lack of ground truth evidence for fluid composition and gas hydrate abundance deep in the sediment sequence however prohibits us from further assessing the current model of pockmark evolution from the region. A MARUM-MeBo 70 drilling cruise in 2016 aims to advance our understanding of the system by recovering sediments tens of meters below seafloor from two active pockmarks along Vestnesa Ridge. We report pore fluid composition data focusing on dissolved chloride, stable isotopes of water (δ18O and δD), and the isotopic composition of dissolved boron (δ11B). From one of the seepage sites, we detect a saline formation water with two layers where gas hydrates were recovered. This saline formation pore fluid is characterized by elevated chloride concentrations (up to 616 mM), high B/Cl ratios (9 × 10−4 mol/mol), high δ18O and δD isotopic signatures (+0.6‰ and +3.8‰, respectively) and low δ11B signatures (+35.0‰), which collectively hint to a high temperature modification at great depths. Based on the dissolved chloride concentration profiles, we estimated up to 47% of pore space occupied by gas hydrate in the sediments shallower than 11.5 mbsf. The observation of bubble fabric in the recovered gas hydrates ...